2022
DOI: 10.1371/journal.pbio.3001610
|View full text |Cite
|
Sign up to set email alerts
|

An evolutionary conserved detoxification system for membrane lipid–derived peroxyl radicals in Gram-negative bacteria

Abstract: How double-membraned Gram-negative bacteria overcome lipid peroxidation is virtually unknown. Bactericidal antibiotics and superoxide ion stress stimulate the transcription of the Burkholderia cenocepacia bcnA gene that encodes a secreted lipocalin. bcnA gene orthologs are conserved in bacteria and generally linked to a conserved upstream gene encoding a cytochrome b561 membrane protein (herein named lcoA, lipocalin-associated cytochrome oxidase gene). Mutants in bcnA, lcoA, and in a gene encoding a conserved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 89 publications
(134 reference statements)
0
6
0
Order By: Relevance
“…Lipids are highly prone to oxidation. MDA is a marker of lipid peroxidation 22 . We next assessed the levels of MDA in both strains.…”
Section: Resultsmentioning
confidence: 99%
“…Lipids are highly prone to oxidation. MDA is a marker of lipid peroxidation 22 . We next assessed the levels of MDA in both strains.…”
Section: Resultsmentioning
confidence: 99%
“…However, in our current study, the overexpression of ADAMTS-15 led to a poor prognosis of patients with LUAD. Recent study has found that the expression of BCNA gene can protect bacterial cell capsule from lipid peroxidation free radicals; however, its exact roles in cancer require to be further studied ( Naguib et al, 2022 ). In our study, BCNA was risk factors, and the patients with highexpression had a poor prognosis, which provided evidence for further study in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Pertinently, analogous to animal lipocalins, plant lipocalins could also be protectively involved in the scavenging of lipid peroxidation intermediates (Boca et al, 2014). Bacterial lipocalins have also been implicated as components of an evolutionarily conserved peroxidation detoxification mechanism that protects the bacterial cell envelope from lipid peroxyl radicals (Naguib et al, 2022), and a similar protective function for plant lipocalins is highly probable. Moreover, vindoline production has been linked with reactive oxygen species burst induced by exogenous stress cues like H 2 O 2 , indicating an antioxidant function of alkaloids like vindoline in plant protection (Tang et al, 2009).…”
Section: Stress Responsiveness Of Crtilmentioning
confidence: 99%